Estimation of thermal maturity in the Bakken source rock from a combination of well logs, North Dakota, USA. (July 2019) - Abarghani, Arash; Ostadhassan, Mehdi; Bubach, Bailey; Zhao, Peiqiang
Abstract: Numerous attempts have been conducted to construct a reliable model to relate petrophysical and geomechanical characteristics of shale to geochemical properties. In this study, continuous logs were built to predict the thermal maturity of the Bakken Formation from a set of petrophysical logs. First, dynamic modulus (Ed ) was created from shear and compressional sonic and, density logs and then converted to Ei (nanoindentation based Young's modulus) using the existing experimental relationship between Ed and Ei . Next, continuous TOC logs were generated for the Bakken Shales based on an empirical relationship between well log derived Ei and TOC contents that were measured in the lab. There was found an acceptable difference between estimated log-based TOC and measured values in three separate wells. Solid bitumen reflectance as a reliable indicator of thermal maturity was measured on all samples from the same wells in the scarcity/absence of vitrinite maceral. The relationships between GR/NPHI/RHOZ wireline logs versus solid bitumen reflectance (BRO %) as the maturity index was then investigated in twelve wells. Based on the strength or weight of the relationship between each log and BRO %, a new parameter "Ʈ" was defined to represent thermal maturity from well logs. A good agreement between parameter Ʈ and BRO % values was observed which provided an empirical equation to make the estimation of BRO % values for the whole length of the shale members possible. Ultimately, the continuity of BRO % values, would enable us to establish a relationship between BRO % and measured Tmax values to generate continuous Tmax logs for the Bakken Shale members. Using these newly developed well logs, it would become possible to make a 3D property models for BRO % and Tmax (the thermal maturity property cube) for an accurate petroleum system evaluation based on GR/NPHI/RHOZ logs. Highlights: A log-based continuous estimation of thermal maturity in source rocks is developed. A new parameter "Ʈ" based on relationships between GR, CNL-FDC logs and solid bitumen reflectance is defined. BRO % logs for the entire interval (depth) of the source rock (UB and LB) to interpret thermal maturity is developed.